Églises doubles et groupes d'églises du point de vue de l'histoire de la liturgie - Gy, Pierre-Marie (Antiquité Tardive - Late Antiquity - Spätantike - Tarda Antichità, 1997)
Abstract The author begins with some thoughts on vocabulary: ecclesia usually refers to the community of the faithful and not to the building, a rather late meaning of the word; ecclesia mater is a metaphor or later designates the mother church of a diocese, not the main building of a group of churches; ecclesia major does not necessarily imply a ecclesia minor. He stresses also that the common distinction in the 4th and 5th centuries between fideles and catechumeni may have had consequences for the physical organization of the church. The author then reviews some liturgical documents. The ordines from Trier, Paris and Lyon are not earlier than the 13th century and make no distinction between liturgical function for different buildings. The ordines from Milan and a church in northern Italy (probably Aquileia according to G. C. Menis and P. Piva) mention the separate distinction in the 11th century (since when ?) between ecclesia hiemalis and ecclesia aestiva and allude to scrutini for the catechumens, who, however, were children at this time. The medieval distinction between ecclesia clericorum and ecclesia laicorum is linked to the internal division of the main building by the rood-screen. The notion of cura animarum is a modern one. The cult of martyrs does not necessarily imply a separate church, since the Eucharist is also celebrated in those churches dedicated to a martyr. The distinction between the liturgy of the Word and the liturgy of the Eucharist is valid only for the Early Church and implies separate locations for the fideles and the catechumeni, not buildings for the two liturgies. The liturgy of baptism during the Easter Vigil may have implied different spaces.